Comparison of conventional and ECO transportation pavements in cyprus using life cycle approach - Achilleos, Constantia; Hadjimitsis, Diofantos G. (My University, 2010)
Road industry has challenged the prospect of ecoconstruction. Pavements may fit within the framework of sustainable development. Hence, research implements assessments of conventional pavements impacts on environment in use of life cycle approach. To meet global, and often national, targets on pollution control, newly introduced pavement designs are under study. This is the case of Cyprus demonstration, which occurred within EcoLanes project work. This alternative pavement differs on concrete layer reinforced with tire recycling product. Processing of post-consumer tires produces steel fibers improving strength capacity against cracking. Thus maintenance works are relevantly limited in comparison to flexible pavement. This enables to be more ecofriendly, referenced to current study outputs. More specific, proposed concrete pavement life cycle processes emits 15% less air pollutants and consumes 28% less embodied energy than those of the asphalt pavement. In addition there is also a reduction on costs by 0.06%.
Keywords: Air pollutants; Concrete layer; Embodied energy; Flexible pavements; Life cycle approach; Life-cycle process; Maintenance work; Pavement design; Post-consumer; Project work; Recycling products; Steel fibers; Strength capacity; Using life; Air pollution; Concrete construction; Environmental impact; Environmental impact assessments; Life cycle; Pollution control; Recycling; Spinning (fibers); Sustainable development; Tires; Pavements; Eco-friendly